Relationship between glycemic control and OPG gene polymorphisms with lower bone mineral density in patients with type 1 Diabetes mellitus - Melina Bezerra Loureiro; Marcela Abbott Galvão Ururahy; Karla Simone Costa de Souza; Yonara Monique da Costa Oliveira; Heglayne Pereira Vital da Silva; Raul Hernandes Bortolin; João Felipe Bezerra; Rosario Dominguez Crespo Hirata; José Jorge Maciel-Neto; Ricardo Fernando Arrais; Maria das Graças Almeida; Mario Hiroyuki Hirata; et al. (Universidade de São Paulo, 2018)
ABSTRACT The aim of the present study was to investigate the bone mineral density (BMD) of patients with type 1 Diabetes mellitus (T1DM). We also assessed the association between osteoprotegerin (OPG) genetic polymorphisms and BMD. Genotyping was performed for 1181G>C and 163A>G OPG polymorphisms by allelic discrimination in 119 patients with T1DM and 161 normoglycemic (NG) individuals, aged 6 to 20 years old. Glycemic control, serum parameters of bone metabolism and BMD were evaluated. T1DM patients showed low BMD, poor glycemic control and decreased total calcium values when compared to controls (p < 0.05). For all the polymorphisms studied, the genotype and allele frequencies in patients with T1DM were not significantly different from the controls. In patients with T1DM, carriers of OPG 1181CC showed higher concentrations of ionized calcium compared to patients with GG+GC genotypes. These results suggest that low BMD is associated with poor glycemic control in T1DM. Despite the lack of a detected association between OPG polymorphisms and BMD in these patients, the increased ionized calcium in those carrying OPG 1181CC suggests a possible increase in osteoclastogenesis, a conclusion that may be supported by the lower BMD observed in these subjects.